2010
DOI: 10.1001/archinternmed.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Information Technology and Teleintensivist Coverage With Decreased Mortality and Ventilator Use in Critically Ill Patients

Abstract: The use of HITB-RIC was associated with significantly lower mortality and less ventilator use in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
7

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 38 publications
(47 reference statements)
2
59
0
7
Order By: Relevance
“…We speculate that bedside and off-site team collaboration is an important determinate of favorable associations of a tele-ICU intervention with outcomes. This hypothesis is supported by the observation that studies that failed to detect significant favorable tele-ICU associations with outcomes included a pathway for bedside physicians to decline participation of the off-site team in patient care, while our workflow processes and other studies reporting significant favorable associations with outcomes for a tele-ICU intervention 20,[35][36][37] did not provide an opt-out pathway.…”
Section: Tele-icu Reengineering Of Critical Care Processessupporting
confidence: 65%
“…We speculate that bedside and off-site team collaboration is an important determinate of favorable associations of a tele-ICU intervention with outcomes. This hypothesis is supported by the observation that studies that failed to detect significant favorable tele-ICU associations with outcomes included a pathway for bedside physicians to decline participation of the off-site team in patient care, while our workflow processes and other studies reporting significant favorable associations with outcomes for a tele-ICU intervention 20,[35][36][37] did not provide an opt-out pathway.…”
Section: Tele-icu Reengineering Of Critical Care Processessupporting
confidence: 65%
“…Previous studies in tele-ICU have suffered from an inability to standardize practice to all patients in the covered ICUs [12,15]. In contrast, in centers where tele-ICU interventions were mandatory and uniform, a mortality benefit was demonstrated [8,17]. We found that, by limiting the tele-ICU team to consultative care, bedside providers were more accepting and that the primary surgical teams allowed all of their patients to participate.…”
Section: E13mentioning
confidence: 73%
“…For example, McCambridge et al [17] characterized the tele-ICU as one component of a coordinated health care information technology bundle. The governance structure of ICU care within the University of Massachusetts-Memorial health care system was restructured and centralized before a tele-ICU implementation [3].…”
Section: E13mentioning
confidence: 99%
See 2 more Smart Citations